Optimal configuration assessments of hybrid renewable power supply for rural healthcare facilities - Lanre Olatomiwa (Energy Reports, 2016)
This paper assessed optimal configurations of hybrid renewable system for rural health clinic (RHC) application in three grid-unconnected rural villages in Nigeria. The RHC consist of an emergency room, consulting room, nurse/injection room, male ward, female ward, a delivery room and a laboratory with average total daily energy consumption of 15.5 kWh and 2.75 kW peak demand. The assessment of configurations that optimally meet the daily load demand with zero loss of power supply probability (LPSP) was carried out using HOMER software, by considering three energy resources; photovoltaic (PV), wind and diesel with battery energy storage. The result obtained revealed hybrid PV/wind/diesel/battery system as the most cost-effective configuration for powering rural health clinic in both Maiduguri and Enugu sites, while that of Iseyin site was found to be hybrid PV/diesel/battery system. In all the sites, the selected optimal configuration is far better than the conventional diesel stand-alone system in terms of cost and emission reduction.
Keywords: 330; HOMER; Hybrid energy system; Nigeria; Optimization; Rural health clinic